2020
DOI: 10.1016/j.heliyon.2020.e04948
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative desiccation tolerance in Eragrostiella brachyphylla: biochemical and physiological responses

Abstract: Eragrostiella brachyphylla is an angiosperm desiccation-tolerant resurrection plant, which can survive during desiccation in the air-dry state and recover completely on availability of water. The present study was conducted to understand the vegetative desiccation tolerance of Eragrostiella brachyphylla by evaluating its ability to recover the physiological, biochemical and morphological functions post desiccation. In order to understand the responses of Eragrostiella brachyphylla to desiccation and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…These results indicate that starch represents a transient energy source in both SEs and ZEs. Most importantly, they imply the preparation of the embryos in a dry state, where the starch content is low after conversion into sugars such as sucrose and RFOs, which helps to prevent lethal effects of water stress ( Yathisha et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that starch represents a transient energy source in both SEs and ZEs. Most importantly, they imply the preparation of the embryos in a dry state, where the starch content is low after conversion into sugars such as sucrose and RFOs, which helps to prevent lethal effects of water stress ( Yathisha et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Anhydrobiosis can be a normal stage of life, as in the case of plant seeds 2,3 , or it can be a response to an environmental loss of water. [4][5][6][7] In many organisms capable of anhydrobiosis, nonreducing sugars such as sucrose in plants 8 or trehalose in many organisms [9][10][11][12][13] are accumulated intracellularly during the process of desiccation. The acquisition of simple polysaccharides was long thought to be an essential feature in desiccation tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Many desiccation-tolerant organisms protect their cells from drying induced damage by accumulating non-reducing sugars, such as sucrose 5 or trehalose. 610 The enrichment of disaccharides was long thought to be a universal feature of desiccation tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst lycophytes, Selaginella (Selaginellaceae) is a commonly occurring genus on rock outcrops. Globally, 25 species of Selaginella are known for their DT properties (Alpert 2000, Kessler and Siorak 2007, Yu et al 2017, Rabarimanarivo et al 2019, Shivaraj et al 2020, Marks et al 2021). Recently, S. bryopteris (Deeba et al 2009) and Selaginella brachystachya (Shivaraj et al 2020) were reported from India as DT species.…”
Section: Discussionmentioning
confidence: 99%
“…Watve (2005) also highlighted the importance of this region in the knowledge of Indian DT plants. Apart from these two works from WG, a few attempts from other Indian regions (Deeba et al 2009, Sharma et al 2015, Lubaina et al 2016, Banupriya et al 2020, Shivaraj et al 2020, 2021) have been carried out to document DT plants. However, a comprehensive documentation of Indian DT species is altogether lacking.…”
Section: Introductionmentioning
confidence: 99%